2020
DOI: 10.1109/access.2020.3016740
|View full text |Cite
|
Sign up to set email alerts
|

EMD-Based Borehole TEM Array Signal Denoising and Baseline Wander Correction for NDT of Downhole Casings

Abstract: Transient electromagnetic (TEM) techniques have been proven to be efficient for nondestructive testing (NDT) operations due to their pulsed eddy-current properties. However, in the field of downhole measurements, harsh environments may significantly influence the NDT performance in downhole casings. In this paper, an empirical mode decomposition (EMD) method based on borehole TEM array signal denoising and baseline wander (BW) correction is proposed to compensate for the bad measurement conditions that affect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Notably, in the derivation above, although G T (t, d) was unknown, it was not used directly. As an alternative, XzG T (t, d) was involved in (12) and could be obtained from the receiving signal. Therefore, the modification of the LCMV subjection did not influence the realization of the MTF method.…”
Section: B Modified Lcmv-based Mtfmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, in the derivation above, although G T (t, d) was unknown, it was not used directly. As an alternative, XzG T (t, d) was involved in (12) and could be obtained from the receiving signal. Therefore, the modification of the LCMV subjection did not influence the realization of the MTF method.…”
Section: B Modified Lcmv-based Mtfmentioning
confidence: 99%
“…NDT techniques, the design of eddy-current sensors as well as their signal processing for borehole measurements are strongly restricted by harsh environments, including narrow underground confined spaces [9], the large temperature range [10], and cumbrous metal tool housings against high wellbore pressure [11], which greatly affect the performance of borehole NDTs [12], [13].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, some previous studies focused on optimizing the PEC probe design for defect detection and revealed that the level of sensitivity of PEC probes can be improved by optimizing the probe design parameters and using magnetic sensors in place of conventional pickup coils [23,24]. Based on this, considering the limited space and high temperatures, approaches for designing PEC sensors and processing signals have been proposed to improve the performance of borehole PEC systems [25][26][27]. In [25,26], a probe with a single transmitter and multiple receivers was designed, and the array output was weighed to eliminate the influence of transmitting-receiving distance and correct the baseline wander caused by the variation in the temperature and motion measurement.…”
Section: Introductionmentioning
confidence: 99%
“…Based on this, considering the limited space and high temperatures, approaches for designing PEC sensors and processing signals have been proposed to improve the performance of borehole PEC systems [25][26][27]. In [25,26], a probe with a single transmitter and multiple receivers was designed, and the array output was weighed to eliminate the influence of transmitting-receiving distance and correct the baseline wander caused by the variation in the temperature and motion measurement. Authors in [27] employed multiple transmitters to realize the magnetic focusing by weighing the current of each transmitter.…”
Section: Introductionmentioning
confidence: 99%
“…Wellbore casing electromagnetic (EM) inspection data is well-known in its difficulty in interpretation (Martin et al 2017, Brill et al 2011), especially when directional information of metal loss is required. A variety of factors such as temperature drift, inspection tool movement speed, baseline wander (Dang et al 2020), and the non-uniformity in casing permeability contributes to the perturbations in EM data. In addition, other conductive wellbore components such as collars often greatly affect EM sensor readings (Sun et al 2022).…”
Section: Introductionmentioning
confidence: 99%